Arctic warriors a personal account of convoy PQ18 - Grossmith Mason, Alfred (Pen & Sword Maritime, 2013)
Publication coincides with the Year of the Convoys. A rare and graphic personal account of this infamously costly convoy. Captures the atmosphere of danger from the enemy and the elements.